The Use of Satellite Information in the Study of the Spatial Organization of Society - Pidgrushnyi, G. P.; Yelistratova, L. O.; Apostolov, O. A.; Provotar, N. I. (Ukrainian Geographical Journal, 2025)
This study aims to develop a methodology for utilizing satellite information to identify functional urbanized territories as the primary forms of spatial organization in society. Based on a comparison between the boundaries of agglomerations determined by the reliability of suburban transportation links and the boundaries of areas with intensive nighttime illumination across Ukraine, it was found that the isoline of illumination intensity above 8% can be used as a conditional boundary of functional urbanized territories. To carry out the typology of functional urbanized territories, the following criteria were defined: the size of the urbanized area in terms of population and land area, the number of centers, population concentration in the cores of functional urbanized areas, and population concentration in urban and rural suburbs. Based on these criteria, a typology was conducted, resulting in the identification of 12 types of functional urbanized territories in Ukraine. It was established that these territories are dynamic entities undergoing the destructive effects of urbicide due to Russian aggression. The scientific novelty of the study lies in the identification of 12 types of functional urbanized territories in Ukraine, which is a crucial component for developing a strategy for post-war recovery of the territory based on their effective development as poles of socio-economic growth. The contribution to scientific discourse is the development of a methodology for typologizing functional urbanized territories using satellite information.